2017
DOI: 10.3177/jnsv.63.269
|View full text |Cite
|
Sign up to set email alerts
|

Agaro-Oligosaccharides Regulate Gut Microbiota and Adipose Tissue Accumulation in Mice

Abstract: Summary Gut microbiota are deeply associated with the prevalence of obesity. Agarose is hydrolyzed easily to yield oligosaccharides, designated as agaro-oligosaccharides (AGO). This study evaluated the effects of AGO on obese phenotype and gut microbial composition in mice. Mice were administered AGO in drinking water (AGO-receiving mice). 16S rRNA gene sequencing analyses revealed their fecal microbiota profiles. Serum bile acids were ascertained using a LC-MS/MS system. Compared to the control group, AGO adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Similar to that observed at 12 weeks, the composition of gastric microbiota in the HFD group at 24 weeks remained distinctly different from that in the CD group, which suggests the permanent effect of HFD on gastric microbiota. Consistent with previous studies, we found an increase in the abundance of gastric microbiota such as Rikenellaceae and Lachnospiraceae , which have been reported to be positively correlated with epididymal adipose tissue weight ( Higashimura et al, 2017 ). The enrichment of Desulfovibrio , which belongs to the family Desulfovibrionaceae , was also observed in the stomach of HFD-fed mice.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to that observed at 12 weeks, the composition of gastric microbiota in the HFD group at 24 weeks remained distinctly different from that in the CD group, which suggests the permanent effect of HFD on gastric microbiota. Consistent with previous studies, we found an increase in the abundance of gastric microbiota such as Rikenellaceae and Lachnospiraceae , which have been reported to be positively correlated with epididymal adipose tissue weight ( Higashimura et al, 2017 ). The enrichment of Desulfovibrio , which belongs to the family Desulfovibrionaceae , was also observed in the stomach of HFD-fed mice.…”
Section: Discussionsupporting
confidence: 92%
“…All of these findings point to a crucial role of Lachnospiraceae to gut health, and therefore the increase in relative abundance of this group can be considered a beneficial effect associated with the consumption of raspberry in this current study. However, members of the family Lachnospiraceae were found to be more abundant in infants of overweight mothers [48] and in obese subjects [49] and have also been shown to be positively correlated with epididymal adipose tissue [50], thus raising concerns with regard to any potential beneficial effect associated with this bacterial group (please note that we and others have shown that some OTUs may be lower or higher in abundance based on diet, even from the same taxa, thus reflecting the well-known variability at the strain level). It is also important to point out that the results of alpha metrics were unexpected based on the differences in several abundant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Agar is widely used in the food, biological, and pharmaceutical industries [3]. Accumulating reports have indicated that the oligosaccharides prepared from agar/agarose have diverse physiological functions, such as antioxidant [4][5][6][7][8][9], anti-hyperlipidemia [9][10][11], anti-inflammation [12][13][14] activity, and a whitening effect [15,16], which will expand their use in the food, cosmetic, and medical industries.…”
Section: Introductionmentioning
confidence: 99%